Artificial intelligence-driven approach for patient-focused drug development - Karmalkar, Prathamesh; Gurulingappa, Harsha; Spies, Erica; Flynn, Jennifer A. (Frontiers in Artificial Intelligence, 2023)
Patients' increasing digital participation provides an opportunity to pursue patient-centric research and drug development by understanding their needs. Social media has proved to be one of the most useful data sources when it comes to understanding a company's potential audience to drive more targeted impact. Navigating through an ocean of information is a tedious task where techniques such as artificial intelligence and text analytics have proven effective in identifying relevant posts for health care business questions. Here, we present an enterprise-ready, scalable workflow demonstrating the feasibility and utility of social media-based patient experience data for use in research and development through capturing and assessing patient experiences and expectations on disease, treatment options, and unmet needs while creating a playbook for roll-out to other indications and therapeutic areas.